Planning and Design of Corrosion Rate Equipment - Saputra, Doni; Dalil, M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Corrosion is natural process that occurred in metal structure. In the planning of construction, metal is the important part of construction. Yet it is often, corrosion phenomenon occurred due to interface with corrosive environment. In the design process, it is need to consider the metal behavior on how much the corrosion rate occurred for a certain time in order to confirm the metal structure application. This equipment is built to support the knowledge of corrosion rate for metal. The experiment shows the result of three specimens regarding the corrosion rates. The corrosive condition is created to trigger the corrosion process where the comparison corrosion rate between sub-soil water and peat water contribute to significance impact of corrosion process.